2022
DOI: 10.1371/journal.pdig.0000057
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a deep learning, value-based care model to predict mortality and comorbidities from chest radiographs in COVID-19

Abstract: We validate a deep learning model predicting comorbidities from frontal chest radiographs (CXRs) in patients with coronavirus disease 2019 (COVID-19) and compare the model’s performance with hierarchical condition category (HCC) and mortality outcomes in COVID-19. The model was trained and tested on 14,121 ambulatory frontal CXRs from 2010 to 2019 at a single institution, modeling select comorbidities using the value-based Medicare Advantage HCC Risk Adjustment Model. Sex, age, HCC codes, and risk adjustment f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…Negative controls, henceforth referred to as controls, were chosen to mimic the deployment environment, and because the DL model would be deployed on all adult CXRs, controls including all available CXRs in the date range above were utilized, along with cases of T2D. The labels for imaging training were based on ICD10 Hierarchical Condition Category (HCC) codes (2021 model 24) for six disease classes, including T2D, congestive heart failure, cardiac arrhythmias, morbid obesity, chronic obstructive pulmonary disease, and vascular disease 21 . Codes mapped to a category were binary encoded to 1 (True), and absent codes mapped to 0 (False), utilizing the most recent codes as of December 2021.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Negative controls, henceforth referred to as controls, were chosen to mimic the deployment environment, and because the DL model would be deployed on all adult CXRs, controls including all available CXRs in the date range above were utilized, along with cases of T2D. The labels for imaging training were based on ICD10 Hierarchical Condition Category (HCC) codes (2021 model 24) for six disease classes, including T2D, congestive heart failure, cardiac arrhythmias, morbid obesity, chronic obstructive pulmonary disease, and vascular disease 21 . Codes mapped to a category were binary encoded to 1 (True), and absent codes mapped to 0 (False), utilizing the most recent codes as of December 2021.…”
Section: Methodsmentioning
confidence: 99%
“…Research has already demonstrated how DL with abdominal computed tomography imaging can detect numerous biomarkers predictive of, for example, metabolic syndrome in asymptomatic adults 18 . Likewise, DL with chest radiography has been shown to predict future healthcare expenses, health disparities, and multiple comorbidities 19 21 . Because of limitations around BMI, we aimed to explore the use of a multitask DL model to detect prevalent T2D from ambulatory frontal CXRs in a large clinical dataset.…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, given the inability to extract DICOM images from JPEG, all Chest X-Rays (CXR) were extracted from the PACS system utilizing a scripted method (SikuliX, 2.0.2) and saved in an encrypted laptop as high-quality 24-bit JPEG files (1669 × 1538 to 3032 × 2520 pixels). CXR analysis used for one particular deep learning algorithm predicting comorbidities and clinical outcome details was established in published work [ 11 , 12 ]. A solution to this issue may be to use a web environment with optional de-identification of imaging data to facilitate data distribution within a hospital environment [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…We successfully created models and compared our results with other published models. These models were published in journals [9][10][11][12] and presented at national conferences. However, translation of such models to the clinical setting proved difficult, partly due to the malalignment of incentives throughout our hospital organization.…”
Section: Theme 4: Model Buildingmentioning
confidence: 99%
See 1 more Smart Citation